DISP-13. FEMALE MICE HAVE GREATER SUSTAINED ACTIVITY SUPPRESSION AND HYPERSOMNOLENCE AFTER RADIATION THERAPY: EXPLORATION OF SEX DIFFERENCES IN A MODEL OF CRANIAL-RADIATION-INDUCED HYPERSOMNOLENCE (C-RIH). (14th November 2022) - Adegbesan, Kendra; Ardori, Francesco Tomassoni; Yanpallewar, Sudhirkumar; Bradley, Sean; Chudasama, Yogita; Briceno, Nicole; King, Amanda; Tessarollo, Lino; Gilbert, Mark; Smart, DeeDee; Armstrong, Terri; Shuboni-Mulligan, Dorela
Abstract: Female cancer patients have a better prognosis but more adverse events with chemotherapy; less is known with other cancer treatments like radiation therapy. Previous literature has demonstrated sex-dependent effects on the hippocampi and behavioral tasks within post-natal mice after radiotherapy. We explored the differences in activity and sleep in adult male and female mice within our previously established mouse model of cranial-irradiation-induced hypersomnolence (C-RIH). Ten mice of each sex (B6 x B6D2 backcrossed with C57/b6NCr) were observed for general activity and sleep continuously over 10 days before and after therapeutic irradiation (whole brain, 15Gy, single fraction). Behavioral assessments aimed at measuring anxiety (Light Dark Box, Elevated Zero Maze) and depression (Sucrose Preference Test) related behaviors, and working memory (Y Maze) were then used to assess any radiation-induced changes in mood or cognition. Independent samples t-tests compared male and female cohorts before and after radiation. At baseline, females had significantly higher peak activity (p < 0.001), as well as day (p < 0.001), and night (p = 0.004) activity. Females also showed less anxiety in the Elevated Zero Maze (p < 0.001) and Light-Dark Box (p = 0.012). In the Y-Maze, females had significantly more alternations (entry into each arm without repeat) (p = 0.004). Males and females consumed the same proportion of sucrose solution in respect to water (p = 0.124). After radiation, males and females showed a significant decrease in activity, with females displaying a higher suppression of night activity both 1-3 days (t(18) = 2.162, p = 0.045) and 7-9 days (t(18) = 2.266, p = 0.037). Female mice also showed increased night hypersomnolence at 1-3 days (t(18) = 4.474, < p = 0.001) and 7-9 days (t(18) = 2.920, p = 0.01). Further analysis is underway on post-radiation sex differences in sleep and activity. Here we used a mouse model of C-RIH to assess the behavioral outcomes between the sexes and found marked effects on sleep and activity.